Enabling Parallel Processing at the Edge for Real-Time Video Analysis Applications - Chaves, Rafael C.; Souza, Lucas M.; Ramos Neto, Otacílio A.; Gomes, Ruan D. (Anais do Workshop de Pesquisa Experimental da Internet do Futuro (WPEIF), 2025)
In the context of video analysis systems, distributed processing is a widely recognized strategy for handling large volumes of data and reducing the execution time of complex tasks. In this paper, we present a solution, called Prisma, designed to enable parallel processing by implementing video stream-splitting strategies, which generate multiple derived streams from the original video stream. These derived streams can be distributed to multiple clients, allowing each processing instance to handle only a portion of the original stream while abstracting the complexities of network management and video fragmentation.